PEMBERDAYAAN MASYARAKAT DALAM PELESTARIAN DAN PEMANFAATAN SUMBERDAYA BUDAYA (STUDI KASUS DI SITUS CANDI MORANGAN) - Masyhudi (BRIN, 2004)
Given the limited number of cultural resources (finite), non-renewable, non-movable, and fragile, the use of cultural resources must be oriented towards conservation. Therefore, in an effort to utilize cultural resources, it should be used with care. Then in terms of the development of cultural assets, we must also look at the value of various interests, so that the various conflicts of interest that exist can be suppressed as far as possible so that there is no attempt to defeat each other, but mutually beneficial.